RELASI GENDER DALAM MENGHADAPI BENCANA DI KABUPATEN MALAKA, NUSA TENGGARA TIMUR - Pah, Theny I. B. Kurniati (Natapraja, 2016)
Communities in the District of Malaka periodically are hit by floods and droughts caused by climate change. Lack of food makes people have to adjust for the sake of survival. Roles, social relationships, responsibilities and division of labor between men and women also can change when trying to meet the needs of such food as a result of climate change. Matriaki culture is embraced by the people of Malacca and geographical environment often affected influential in the division of labor between men and women every day. Harvard Gender Analysis techniques used in this study to look at the impact of climate change and gender relations are formed in three patterns of food production (production, distribution and consumption) that occurs in the three affected areas in the district of Malaka. Keywords: Disaster, Culture Matriarchy, Gender Analysis Technique Harvard.